Design of Seat Search System in the Classroom Based on Wireless Sensor Networks - chen, Jia Yu; Megxuan, Cui; Megxuan, Cui (International Journal of Online and Biomedical Engineering (iJOE), 2018)
The purpose of this design is intended to statistics and publishes free seats information in classroom timely to students, and then save students’ time to looking for classroom. The system uses wireless sensor networks to monitor classroom vacancies. It consists of classroom monitoring system and information transmission system. The classroom monitoring system consists of a coordinator node for remote wireless communication and two collection nodes for local communications in the classroom, and that three nodes are star-connected. The tasks of the coordinator node are to collect information from the collection nodes and display and transmission. Set up two collection nodes for collecting information of the number who inter the classroom. The devices for counting include two units, signal acquisition unit is constituted with pyroelectric infrared sensor which contains RE200B probe and conditioning circuit, and the control unit is constituted with CC2530 for signal processing. LCD screen is used to real-time display in coordinator node for counting the number of coming in or out the classroom. Users who enter the teaching building check which classroom have seats available. The manner of local communication is using ZIGBEE. The entire system uses sensor technology and mobile network communication technology to achieve real-time acquisition and release of information. The ability to identify and stability of the experimental system currently implemented are strong.